RAYON FILAMENT PROPERTIES FROM FIVE LESSER KNOWN TROPICAL WOODS SPECIES - Wawan Kartiwa Haroen dan Nyoman Wistara (Department of Agroindustrial Technology, Bogor Agricultural University, 2008)
ABSTRACTFive lesser known hardwood species from recently opened settlement area in Kalimantan and Sumatra islands of Indonesia were collected and identified as Symplocos sp., Pterygota sp., Schima sp., Nyssa sp., and Gymnotroches sp. The present experiments were intended to evaluate the potential of these species for dissolving pulp and rayon production. Prehydrolized kraft process was applied to pulp the woods and an ECF bleaching method with DEDED sequences were chosen to purify the resulting pulp. All dissolving pulp and rayon filament properties were compared to Indonesian Industrial Standard SNI 14-0938-1989 for regular rayon filament and high wet modulus (HWM) rayon filament properties. It has been found that these woods can be classified as class II for raw material of pulp making with medium to long fiber, medium wood density and acceptable bulk density of chips. Gymnotroches sp. was the most difficult to delignify, as indicated by the highest kappa number of 18.8. Except for pulp brightness, all parameters tested indicated that these species are highly potential for dissolving pulp and regular rayon production. Some parameters were even indicating that these woods can be used for HWM rayon fiber.Keywords: prehydrolysis, tropical hardwood, dissolving pulp, regular rayon, HWM rayon.